Answer:
The level curves F(t,z) = C for any constant C in the real numbers
where
![F(t,z)=z^3t^2+e^(tz)-4t+2z](https://img.qammunity.org/2020/formulas/mathematics/college/kitma6c2671wb7zf9vf89rv64bolkemloj.png)
Explanation:
Let's call
![M(t,z)=2tz^3+ze^(tz)-4](https://img.qammunity.org/2020/formulas/mathematics/college/huc1drw69ru8iflb0ms91bf1xpwdpdh7js.png)
![N(t,z)=3t^2z^2+te^(tz)+2](https://img.qammunity.org/2020/formulas/mathematics/college/j4f6r32v5cv0cjmq719pqm2refohetqtgo.png)
Then our differential equation can be written in the form
1) M(t,z)dt+N(t,z)dz = 0
To see that is an exact differential equation, we have to show that
2)
![(\partial M)/(\partial z)=(\partial N)/(\partial t)](https://img.qammunity.org/2020/formulas/mathematics/college/t9ttuymesrpv1h5azvnrywhv55xau1i8mk.png)
But
![(\partial M)/(\partial z)=(\partial (2tz^3+ze^(tz)-4))/(\partial z)=6tz^2+e^(tz)+zte^(tz)](https://img.qammunity.org/2020/formulas/mathematics/college/s9lz5r4ty1xl80exex2fvprdmpj9w9j9xz.png)
In this case we are considering t as a constant.
Similarly, now considering z as a constant, we obtain
![(\partial N)/(\partial t)=(\partial (3t^2z^2+te^(tz)+2))/(\partial t)=6tz^2+e^(tz)+zte^(tz)](https://img.qammunity.org/2020/formulas/mathematics/college/n9shybe5rmucbeth82lije4mi6qi2t4pw8.png)
So, equation 2) holds and then, the differential equation 1) is exact.
Now, we know that there exists a function F(t,z) such that
3)
AND
4)
![(\partial F)/(\partial z)=N(t,z)](https://img.qammunity.org/2020/formulas/mathematics/college/ncqip8h4llnxcbysggd8ke3b1rptcq3trq.png)
We have then,
![(\partial F)/(\partial t)=2tz^3+ze^(tz)-4](https://img.qammunity.org/2020/formulas/mathematics/college/pzflg063l1akbohwuxruvzwuruina9ua3r.png)
Integrating on both sides
![F(t,z)=\int (2tz^3+ze^(tz)-4)dt=2z^3\int tdt+z\int e^(tz)dt-4\int dt+g(z)](https://img.qammunity.org/2020/formulas/mathematics/college/bjuilh7193igjufac8n67ey3n10t11jvlf.png)
where g(z) is a function that does not depend on t
so,
![F(t,z)=(2z^3t^2)/(2)+z(e^(tz))/(z)-4t+g(z)=z^3t^2+e^(tz)-4t+g(z)](https://img.qammunity.org/2020/formulas/mathematics/college/8ycz4s0s8vll7sqwm8sl3kwp4imvzsdayt.png)
Taking the derivative of F with respect to z, we get
![(\partial F)/(\partial z)=3z^2t^2+te^(tz)+g'(z)](https://img.qammunity.org/2020/formulas/mathematics/college/dam2zzfgrd7db8uqd4earr8t6v9cq29gjk.png)
Using equation 4)
![3z^2t^2+te^(tz)+g'(z)=3z^2t^2+te^(tz)+2](https://img.qammunity.org/2020/formulas/mathematics/college/lee4jaiel0e35fc4tz0ndvd3asra5f9jif.png)
Hence
![g'(z)=2\Rightarrow g(z)=2z](https://img.qammunity.org/2020/formulas/mathematics/college/zw74c1p8ab85rdtguxoj7f9rgffdofaipf.png)
The function F(t,z) we were looking for is then
![F(t,z)=z^3t^2+e^(tz)-4t+2z](https://img.qammunity.org/2020/formulas/mathematics/college/kitma6c2671wb7zf9vf89rv64bolkemloj.png)
The level curves of this function F and not the function F itself (which is a surface in the space) represent the solutions of the equation 1) given in an implicit form.
That is to say,
The solutions of equation 1) are the curves F(t,z) = C for any constant C in the real numbers.
Attached, there are represented several solutions (for c = 1, 5 and 10)